Surrogate markers of long-term outcome in primary total hip arthroplasty: a systematic review - Malak, T; Broomfield, J; Palmer, A; Hopewell, S; Carr, A; Brown, C; Prieto-Alhambra, D; Glyn-Jones, S (British Editorial Society of Bone and Joint Surgery, 2016)
High failure rates of metal-on-metal hip arthroplasty implants have highlighted the need for more careful introduction and monitoring of new implants and for the evaluation of the safety of medical devices. The National Joint Registry and other regulatory services are unable to detect failing implants at an early enough stage. We aimed to identify validated surrogate markers of long-term outcome in patients undergoing primary total hip arthroplasty (THA).We conducted a systematic review of studies evaluating surrogate markers for predicting long-term outcome in primary THA. Long-term outcome was defined as revision rate of an implant at ten years according to National Institute of Health and Care Excellence guidelines. We conducted a search of Medline and Embase (OVID) databases. Separate search strategies were devised for the Cochrane database and Google Scholar. Each search was performed to include articles from the date of their inception to June 8, 2015.Our search strategy identified 1082 studies of which 115 studies were included for full article review. Following review, 17 articles were found that investigated surrogate markers of long-term outcome. These included one systematic review, one randomised control trial (RCT), one case control study and 13 case series. Validated surrogate markers included Radiostereometric Analysis (RSA) and Einzel-Bild-Röntgen-Analyse (EBRA), each measuring implant migration and wear. We identified five RSA studies (one systematic review and four case series) and four EBRA studies (one RCT and three case series). Patient Reported Outcome Measures (PROMs) at six months have been investigated but have not been validated against long-term outcomes.This systematic review identified two validated surrogate markers of long-term primary THA outcome: RSA and EBRA, each measuring implant migration and wear. We recommend the consideration of RSA in the pre-market testing of new implants. EBRA can be used to investigate acetabular wear but not femoral migration. Further studies are needed to validate the use of PROMs for post-market surveillance.